Behavioural Ecology Traits of Elusive Deep-Diver Whales Unravel a Complex Social Structure Influenced by Female Philopatry and Defence Polygyny - Badenas, Anja; Dinis, Ana; Ferreira, Rita; Sambolino, Annalisa; Hamard, Eliette; Berninsone, Leonardo G.; Fernandez, Marc; Alves, Filipe (Frontiers in Marine Science, 2022)
Knowledge of the role of individual associations has provided an insightful understanding of the structures of animal societies, especially in highly social mammals such as primates. Yet, this is unbalanced towards marine mammals, particularly to beaked whales, due to their elusive nature. In addition, information on the fundamental drivers of the social organisation of these deep-diving animals is still scarce. Here, the hypothesis of female defence polygyny was tested in Blainville’s beaked whales (Mesoplodon densirostris) and discussed within the context of marine and terrestrial organisms displaying similar patterns, by i) estimating residency times to obtain information on the movements into and out of the area, ii) analysing social networks to assess individual association metrics, iii) measuring the strength of the associations to assess the existence of preferred or avoided relationships among individuals, and iv) modelling simulated different social structures to address temporal patterns in social relationships. Using a 9-year photographic dataset derived from the pelagic habitat, individual associations were inferred based on likelihood techniques. The multidimensional approach served as a model system to infer the species' social structure in relation to age class, sex, residency status, and spatio-temporal patterns, which can be a good practice to be applied for other taxa. Heterogeneity in capture probability and residency times was observed between age-sex classes, with adult females exhibiting long-term site fidelity. This suggests different habitat roles and spatial structuring within this social organisation, with resident animals playing a pivotal role. Strong and long dyadic associations occurred between adult females and immatures, contrarily to between males, and the best-fitting models of the temporal patterns included preferred companions and casual acquaintances. The present findings unravel a complex social structure stratified by age-sex class and influenced by female philopatry and defence polygyny, like an unimale group mating system, which varies from other beaked whales but is similar to some birds, pinnipeds, or nonhuman primates.